Addressing Multilevel Program Complexity by Evaluation Design. (September 2015) - Sager, Fritz; Mavrot, Céline; Hadorn, Susanne
Abstract : In this paper, we present the evaluation design for a complex multilevel program recently introduced in Switzerland. The evaluation embraces the federal level, the cantonal program level, and the project level where target groups are directly addressed. We employ Pawson and Tilley's realist evaluation approach, in order to do justice to the varying context factors that impact the cantonal programs leading to varying effectiveness of the implemented activities. The application of the model to the canton of Uri shows that the numerous vertical and horizontal relations play a crucial role for the program's effectiveness. As a general learning for the evaluation of complex programs, we state that there is a need to consider all affected levels of a program and that no monocausal effects can be singled out in programs where multiple interventions address the same problem. Moreover, considering all affected levels of a program can mean going beyond the borders of the actual program organization and including factors that do not directly interfere with the policy delivery as such. In particular, we found that the relationship between the cantonal and the federal level was a crucial organizational factor influencing the effectiveness of the cantonal program.